2012
DOI: 10.1016/j.janxdis.2012.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the association between parenting and adolescent social phobia

Abstract: Paternal behavior appears particularly relevant for SP. The pattern of maternal overprotection, paternal rejection and lower emotional warmth was observed in SP only, suggesting that its detailed assessment provides a promising opportunity for targeted prevention and intervention in SP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 70 publications
8
60
1
2
Order By: Relevance
“…Previous research on familial and parental risk factors for anxiety and depression suggests that especially adverse parental rearing styles and unfavorable characteristics of the parent-child relationship increase the risk for offspring anxiety and depression [11,14,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Particularly the role of parental rearing for offspring anxiety and depression has been extensively studied [11,14,[29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research on familial and parental risk factors for anxiety and depression suggests that especially adverse parental rearing styles and unfavorable characteristics of the parent-child relationship increase the risk for offspring anxiety and depression [11,14,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Particularly the role of parental rearing for offspring anxiety and depression has been extensively studied [11,14,[29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly the role of parental rearing for offspring anxiety and depression has been extensively studied [11,14,[29][30][31][32][33][34]. While parental control was found to be more strongly associated with offspring anxiety than parental rejection, parental rejection was shown to be more strongly associated with offspring depression than parental control [29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Knappe et al ( 2012 ) reported distinct and contrasting patterns of parental dysfunction, such that maternal overprotection and paternal rejection and lower emotional warmth predicted SAD in their children. Interestingly, the crossover relationships were not found to be true-paternal overprotection and maternal rejection or lack of warmth failed to signifi cantly predict SAD in their children (Knappe et al 2012 ).…”
Section: Sad and Family Organizationmentioning
confidence: 80%
“…Ruiter and van Ijzendoorn (1992) also carried out research confirming the relationship between attachment issues and agoraphobia. In terms of social phobia, there are a number of recent studies that confirm the association of insecure attachment with the development of social phobia (Knappe et al 2012). Bowlby (1973) demonstrated the impact of poor attachment with school phobia and agoraphobia; Klein (1964) reported on a sample of female adult patients with panic and agoraphobia having a history of separation anxiety or school phobia.…”
Section: Literature Reviewmentioning
confidence: 99%